Methylation-Specific Oligonucleotide Microarray: A New Potential for High-Throughput Methylation Analysis - Gitan, Raad S.; Shi, Huidong; Chen, Chuan-Mu; Yan, Pearlly S.; Huang, Tim Hui-Ming (Genome Research, 2002)
Oligonucleotide microarray-based hybridization is an emerging technology for genome-wide detection of DNA variations. We have extended this principle and developed a novel approach, called methylation-specific oligonucleotide (MSO) microarray, for detecting changes of DNA methylation in cancer. The method uses bisulfite-modified DNA as a template for PCR amplification, resulting in conversion of unmethylated cytosine, but not methylated cytosine, into thymine within CpG islands of interest. The amplified product, therefore, may contain a pool of DNA fragments with altered nucleotide sequences due to differential methylation status. A test sample is hybridized to a set of oligonucleotide (19–23 nucleotides in length) arrays that discriminate methylated and unmethylated cytosine at specific nucleotide positions, and quantitative differences in hybridization are determined by fluorescence analysis. A unique control system is also implemented to test the accuracy and reproducibility of oligonucleotides designed for microarray hybridization. This MSO microarray was applied to map methylated CpG sites within the humanestrogen receptor α (ERα) gene CpG island in breast cancer cell lines, normal fibroblasts, breast tumors, and normal controls. Methylation patterns of the breast cancer cell lines, determined by MSO microarray, were further validated by bisulfite nucleotide sequencing (P <0.001). This proof-of-principle study shows that MSO microarray is a promising technique for mapping methylation changes in multiple CpG island loci and for generating epigenetic profiles in cancer.[The sequence data described in this paper have been submitted to the data library under accession no. X03635.1 G1:31233.]